Comprehensive Metabolome and Volatilome Analyses in Eggplant and Tomato Reveal Their Differential Responses to Tuta absoluta Infestation - Chen, Limin; Li, Xiaowei; Zhang, Jinming; He, Tianjun; Huang, Jun; Zhang, Zhijun; Wang, Yeyang; Hafeez, Muhammad; Zhou, Shuxing; Ren, Xiaoyun; Hou, Youming; Lu, Yaobin (Frontiers in Plant Science, 2021)
South American tomato pinworm, Tuta absoluta, is one of the most destructive insect pests in Sol-anaceae crops, particularly tomato. Current methods of management have proven somewhat ef-fective but still requires a more efficacious management strategy to limit its havoc on crop yield. Tomato is much more predisposed to T. absoluta as compared to other plants such as eggplant, but the underlying causes have not been fully determined. We conducted this study to unravel volatile organic compounds (VOCs) and primary/secondary metabolites that account for differential re-sponse of tomato and eggplant to T. absoluta infestation. We performed widely targeted compara-tive metabolome and volatilome profiling using the UPLC-MS/MS and HS-SPME/GC-MS, re-spectively on eggplant and tomato under control and T. absoluta infestation conditions. Overall, 141 VOCs and 797 primary/secondary metabolites were identified, largely dominated by alde-hyde, alcohols, alkanes, amine, aromatics, heterocyclic compound, ketone, olefin, phenol and ter-penes. Most of the VOCs and primary/secondary metabolites from terpene class were largely dif-ferentially regulated in eggplant compared to tomato. Eggplant emitted a number of compounds that were lower or completely absent in tomato either under control condition or after T. absoluta infestation. The results from electroantennogram showed that 35 differentially accumulated vol-atile organic compounds could elicit female T. absoluta response, implying that these volatile compounds significantly alter the behavior of this pest. These findings demonstrated that differ-entially accumulated metabolites and volatile compounds play major roles in eggplant resistance to T. absoluta infestation as these compounds were regulated upon attack by T. absoluta. Our find-ings can assist in integrated pest management efforts by developing appropriate control measures against T. absoluta in Solanaceae production.